2021
DOI: 10.3390/plants10102099
|View full text |Cite
|
Sign up to set email alerts
|

QTL Validation and Development of SNP-Based High Throughput Molecular Markers Targeting a Genomic Region Conferring Narrow Root Cone Angle in Aerobic Rice Production Systems

Abstract: Aerobic rice production (AP) provides potential solutions to the global water crisis by consuming less water than traditional permanent water culture. Narrow root cone angle (RCA), development of deeper rooting and associated genomic regions are key for AP adaptation. However, their usefulness depends on validation across genetic backgrounds and development of linked markers. Using three F2 populations derived from IRAT109, qRCA4 was shown to be effective in multiple backgrounds, explaining 9.3–17.3% of the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The KASP assay has also been instrumental in uncovering the genetic basis of important traits in rice. In another study he identified 12 markers associated with narrow root cone angle [41], while indifferent study [42] they identify 110 markers associated with grain yield and adaptability traits. According to another study Tang et al [43] identified 48 markers for variety identification and breeding guidance.…”
Section: Kasp Markers In Plant Breedingmentioning
confidence: 99%
“…The KASP assay has also been instrumental in uncovering the genetic basis of important traits in rice. In another study he identified 12 markers associated with narrow root cone angle [41], while indifferent study [42] they identify 110 markers associated with grain yield and adaptability traits. According to another study Tang et al [43] identified 48 markers for variety identification and breeding guidance.…”
Section: Kasp Markers In Plant Breedingmentioning
confidence: 99%
“…This type of utility was highlighted recently in an elite breeding core panel where several high-value disease and insect resistance genes were present at considerable frequencies (although not fixed) and thus represent haplotypes/alleles that are easily selectable in existing breeding populations (Juma et al, 2021). After successful QTL validation, molecular markers could be designed for their survey and introgression in breeding programs (Vinarao et al, 2021a). An assessment of high throughput molecular markers in rice showed that only two QTL for seedling LT tolerance, SCT1, and COLD1, were developed for this purpose 3 indicating the opportunity to develop markers for reproductive stage LT tolerance.…”
Section: Genomic Regions Associated With Lt Tolerance At Ymsmentioning
confidence: 99%
“…High throughput root phenotyping generates adequate and high quality data to enrich simulation models for root selection programmes (Muller & Martre, 2019). There is intraspecific and interspecific variation for various root parameters such as root angle, length, density and biomass useful for selection programmes in diverse genetic resources including landrace, old and modern varieties of crops such as sorghum, wheat, soybean, maize and rice (Bernardino et al, 2019; Mathew et al, 2018; Prince et al, 2020; Moussa et al, 2021, Vinarao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%